Candida albicans and Pseudomonas aeruginosa Interaction, with Focus on the Role of Eicosanoids - Fourie, Ruan; Ells, Ruan; Swart, Chantel W.; Sebolai, Olihile M.; Albertyn, Jacobus; Pohl, Carolina H. (Frontiers in Physiology, 2016)
Candida albicans is commonly found in mixed infections with Pseudomonas aeruginosa, especially in the lungs of cystic fibrosis patients. Both of these opportunistic pathogens are able to form resistant biofilms and frequently infect immunocompromised individuals. The interaction between these two pathogens, which includes physical interaction as well as secreted factors, is mainly antagonistic. In addition, research suggests considerable interaction with their host, especially with immunomodulatory lipid mediators, termed eicosanoids. Candida albicans and Pseudomonas aeruginosa are both able to utilize arachidonic acid, liberated from the host cells during infection, to form eicosanoids. The production of these eicosanoids, such as Prostaglandin E2, by the host and the pathogens may affect the dynamics of polymicrobial infection and the outcome of infections. It is therefore of considerable importance to elucidate the role of host-produced, as well as pathogen-produced eicosanoids in polymicrobial infection. This review will focus on in vitro as well as in vivo interaction between C. albicans and P. aeruginosa, paying special attention to the role of eicosanoids in the cross-talk between host and the pathogens.